SMS application with unlimited service registration and indicator - Bustamante, Leonardo Jr. B.
Instant Messaging (IM) is becoming the key technology for corporate collaboration and communication. It provides businesses and companies an efficient way of communicating with customers and employees. Commercially available products and services usually provide maintenance and database support for messages. However, users are left with minimal control over the messages and the database contents that makes theses products and services expensive and hard to maintain. In addition, users are bound to the additional rates imposed by the software developers. Setting-up and installation of IM servers and other hardware also takes a long period. This paper will discuss the development of a Short Message Service (SMS) application that is intended to address these problems. The application used a SMS library that is Free and Open Source Software (FOSS). An embedded database ported to the application holds messages, profiles and mobile contacts. The application will support as many models of Global System for Mobile (GSM) modems and mobile phones as possible for sending and receiving SMS messages. Siemens MC35i, iTegno 3000, Sony Ericsson phones with DCU-60 data cable, and Nokia phones are some of the GSM modems and mobile phones that the application supports. Installation and utilization of the application will only take minutes, as it will be using the Plug and Play feature of mobile phones and modems. Users may opt to further increase their cost efficiency by utilizing the unlimited feature of their mobile service provider and the message filter through the application. The application can generate registration messages for the unlimited service regardless of the mobile network and can filter recipients' mobile numbers if the numbers belong to other mobile networks. Finally, an easy-to-use and intuitive User Interface (UI) of the application provides users zero training and full control to all features.